العدوى الانفعالية وعلاقتها بالتحصيل الأكاديمي لطلبة قسم اللغة العربية (Journal of the College of Basic Education, 2026)
The current research aims to: Identify the level of emotional infection among students of the Department of Arabic Language. Identify the significance of the differences in the level of emotional infection among students of the Arabic Language Department according to the gender variable (males - females). To achieve the objectives of the research, the steps of the descriptive approach were followed, and the research sample consisted of (140) male and female students from the Department of Arabic Language, and a scale prepared by (Al-Shammari, 2013) was adopted for emotional infection, which consists of (18) paragraph, which falls under five alternatives to the answer: (always, often, rarely, sometimes, never) take when correcting (1,2,3,4,5), as the data was processed statistically using: - T test for one sample - T test for two independent samples The following results were reached: Students of the Arabic Language Department at the College of Education for Human Sciences / University of Anbar have an emotional infection. There are statistically significant differences in academic achievement among students of the Arabic Language Department according to the gender variable (males - females) and in favor of females. Identify the academic level of the students of the Arabic Language Department. Recognize the correlation between emotional infection